Is Meropenem as a Monotherapy Truly Incompetent for Meropenem-Nonsusceptible Bacterial Strains? A Pharmacokinetic/Pharmacodynamic Modeling With Monte Carlo Simulation - Song, Xiangqing; Wu, Yi; Cao, Lizhi; Yao, Dunwu; Long, Minghui (Frontiers in Microbiology, 2019)
Infections due to meropenem-nonsusceptible bacterial strains (MNBSs) with meropenem minimum inhibitory concentrations (MICs) ≥16 mg/L have become an urgent problem. Currently, the optimal treatment strategy for these cases remains uncertain due to some limitations of currently available mono- and combination therapy regimens. Meropenem monotherapy using a high dose of 2 g every 8 h (q 8 h) and a 3-h traditional simple-prolonged-infusion (TSPI) has proven to be helpful for the treatment of infections due to MNBSs with MICs of 4-8 mg/L but is limited for cases with higher MICs of ≥16 mg/L. This study demonstrated that optimized-two-step-administration therapy (OTAT, i.e., a new administration model of i.v. bolus plus prolonged infusion) for meropenem, even in monotherapy, can resolve this problem and was thus an important approach of suppressing such highly resistant-bacterial isolates. Herein, a pharmacokinetic (PK)/pharmacodynamic (PD) modelling with Monte Carlo simulation was performed to calculate the probabilities of target attainment (PTAs) and the cumulative fractions of response (CFRs) provided by dosage regimens and 39 OTAT regimens in 5 dosing models targeting 8 highly resistant bacterial species with meropenem MICs ≥16 mg/L, including Acinetobacter baumannii, Acinetobacter spp, Enterococcus faecalis, Enterococcus faecium, Pseudomonas aeruginosa, Staphylococcus epidermidis, Staphylococcus haemolyticus and Stenotrophomonas maltophilia, were designed and evaluated. The data indicated that meropenem monotherapy administered at a high dose of 2 g q 8 h and as an OTAT achieved a PTA of ≥90% for isolates with an MIC of up to 128 mg/L and a CFR of ≥90% for all of the targeted pathogen populations when 50% fT>MIC (50% of the dosing interval during which free drug concentrations remain above the MIC) is chosen as the PD target, with Enterococcus faecalis being the sole exception. Even though 50% fT>5×MIC is chosen as the PD target, the aforementioned dosage regimen still reached a PTA of ≥90% for isolates with an MIC of up to 32 mg/L and a CFR of ≥90% for Acinetobacter spp, Pseudomonas aeruginosa and Klebsiella pneumoniae populations. In conclusion, meropenem monotherapy displays potential competency for infections due to such highly resistant bacterial isolates provided that it is administered as a reasonable OTAT.